2022
DOI: 10.7189/jogh.12.08001
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition-sensitive agriculture programs increase dietary diversity in children under 5 years: A review and meta-analysis

Abstract: Background Low-quality diets contribute to the burden of malnutrition and increase the risk of children not achieving their developmental potential. Nutrition-sensitive agriculture programs address the underlying determinants of malnutrition, though their contributions to improving diets do not factor into current nutrition impact modeling tools. Objective To synthesize the evidence on the effectiveness of nutrition-sensitive agriculture programs in improving dietary di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…To address this, we not only need effective interventions that address the direct causes of undernutrition (termed ‘nutrition‐specific’ interventions), but also effective ‘nutrition‐sensitive’ interventions that address root causes of undernutrition, such as low agricultural productivity, food insecurity and gender‐based inequities (Bhutta et al, 2013 ; Kadiyala et al, 2014 ). Nutrition‐sensitive agriculture (NSA) interventions offer a means to do this and can improve dietary quality in several settings (Margolies et al, 2022 ). However, they are typically less cost‐effective than nutrition‐specific interventions (Webb et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…To address this, we not only need effective interventions that address the direct causes of undernutrition (termed ‘nutrition‐specific’ interventions), but also effective ‘nutrition‐sensitive’ interventions that address root causes of undernutrition, such as low agricultural productivity, food insecurity and gender‐based inequities (Bhutta et al, 2013 ; Kadiyala et al, 2014 ). Nutrition‐sensitive agriculture (NSA) interventions offer a means to do this and can improve dietary quality in several settings (Margolies et al, 2022 ). However, they are typically less cost‐effective than nutrition‐specific interventions (Webb et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Three I-O pairs for interventions addressing child anaemia were excluded because of the lack of evidence of its association with mortality [ 13 , 32 - 34 ]. Other reasons for excluding I-O pairs included the lack of systematic reviews available on the association of interest, pooled estimates derived from very small study populations (n <400) [ 38 ], an inability to model the impact due to the way data were presented [ 29 ]; the lack of clarity in the definition of the intervention (nutrition-sensitive agriculture which may include more than one intervention – eg, agriculture inputs and BCC) [ 31 ], the absence of country-level data on the outcome of interest (eg, child mortality due to neural tube defects), or the review’s failure to provide estimated impacts of the intervention (eg, the direct impact of SQ-LNS on cause-specific child mortality other than the indirect effect via stunting and wasting). One I-O pair was also excluded because the impact of calcium supplementation on pre-eclampsia might be accounted for in other existing links (calcium and preterm birth, and calcium and maternal mortality due to hypertensive disorder) [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…This study presents full programme costs in the pre‐COVID period and is an important step toward a comprehensive economic evaluation. As noted above, a recent systematic review has found that nutrition‐sensitive agricultural interventions have a significant positive impact on dietary diversity among children 6−60 months old (Margolies et al 2022 ). This paper helps illustrate the costs of these complex interventions, providing a benchmark that can be used to assess costs and affordability of this and similar programmes.…”
Section: Discussionmentioning
confidence: 98%